1997
DOI: 10.1111/j.1749-6632.1997.tb48214.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Camden Study of Adolescent Pregnancy: Interactions Among Maternal Growth, Nutritional Status, and Body Composition

Abstract: One of the principal goals of the Camden Study over the past decade has been to document the extent to which pregnancy during adolescence is affected by continued maternal growth. Findings from the Camden Study relating to the other main goal, the effects of maternal growth during pregnancy on the outcome of pregnancy (maternal-fetal competition), are reviewed elsewhere. Contrary to widely held beliefs, we have found that there is considerable growth in late adolescence for girls, and, in particular, continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…Since maternal malnutrition, micronutrient deficiencies and SGA births remain major determinants of stunting in early childhood, malnutrition prevention has undergone a paradigm shift from targeting pregnant women to an increased advocacy of targeting these deficiencies earlier in the life cycle through promoting adolescent health and nutrition, delaying first pregnancies and increased birth spacing. Adolescent nutrition is also important with regard to maternal nutrition as pregnant adolescents are at risk of adverse outcomes including LBW, preterm delivery, anemia and excessive postpartum weight retention due to a combination of physiological, socioeconomic and behavioral factors [84,85,86]. …”
Section: Way Forwardmentioning
confidence: 99%
“…Since maternal malnutrition, micronutrient deficiencies and SGA births remain major determinants of stunting in early childhood, malnutrition prevention has undergone a paradigm shift from targeting pregnant women to an increased advocacy of targeting these deficiencies earlier in the life cycle through promoting adolescent health and nutrition, delaying first pregnancies and increased birth spacing. Adolescent nutrition is also important with regard to maternal nutrition as pregnant adolescents are at risk of adverse outcomes including LBW, preterm delivery, anemia and excessive postpartum weight retention due to a combination of physiological, socioeconomic and behavioral factors [84,85,86]. …”
Section: Way Forwardmentioning
confidence: 99%
“…This study suggested a marginally constant effect of any BF duration on PPWR in overweight mothers but not in obese women, despite the continuity of BF until 12 months postpartum. Obesity produces physiological changes in body composition, reduction in insulin sensitivity, decreased intention to BF, decreased initiation of BF, and decreased duration of BF [30]. Less The higher percentage of children followed-up at ages 3 (95.7%) and 12 months (94.3%), the nature of data collection and the populationbased recruitment are the strengths of this birth cohort [13].…”
Section: Discussionmentioning
confidence: 96%
“…Given the skepticism around the results in older adults, we further explored this relationship in our dataset using sensitivity analyses. Since some evidence suggests that pregnant adolescents are more likely to become overweight or obese in adulthood(33, 34) and because the underweight category disproportionately included adolescents, we excluded them from the analysis. We also excluded smokers, who may be underweight but have higher mortality, and assessed whether women in the underweight group had more pre-pregnancy co-morbid illnesses, as being underweight could be marker for poor health status.…”
Section: Discussionmentioning
confidence: 99%